Validity and reliability of inertial measurement units measurements for running kinematics in different foot strike pattern runners - Zeng, Ziwei; Liu, Yue; Li, Pan; Wang, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to assess the validity and reliability of the three-dimensional joint kinematic outcomes obtained by the inertial measurement units (IMUs) for runners with rearfoot strike pattern (RFS) and non-rearfoot strike pattern (NRFS). The IMUs system and optical motion capture system were used to simultaneous collect 3D kinematic of lower extremity joint data from participants running at 12km/h. The joint angle waveforms showed a high correlation between the two systems after the offset correction in the sagittal plane (NRFS: coefficient of multiple correlation (CMC)=0.924–0.968, root mean square error (RMSE)=4.6°–13.7°; RFS: CMC=0.930–0.965, RMSE=3.1°–7.7°), but revealed high variability in the frontal and transverse planes (NRFS: CMC=0.924–0.968, RMSE=4.6°–13.7°; RFS: CMC=0.930–0.965, RMSE=3.1°–7.7°). The between-rater and between-day reliability were shown to be very good to excellent in the sagittal plane (between-rater: NRFS: CMC=0.967–0.975, RMSE=1.9°–2.9°, RFS: CMC=0.922–0.989, RMSE=1.0°–2.5°; between-day: NRFS: CMC=0.950–0.978, RMSE=1.6°–2.7°, RFS: CMC=0.920–0.989, RMSE=1.7°–2.2°), whereas the reliability was weak to very good (between-rater: NRFS: CMC=0.480–0.947, RMSE=1.1°–2.7°, RFS: CMC=0.646–0.873, RMSE=0.7°–2.4°; between-day: NRFS: CMC=0.666–0.867, RMSE=0.7°–2.8°, RFS: CMC=0.321–0.805, RMSE=0.9°–5.0°) in the frontal and transverse planes across all joints in both types of runners. The IMUs system was a feasible tool for measuring lower extremity joint kinematics in the sagittal plane during running, especially for RFS runners. However, the joint kinematics data in frontal and transverse planes derived by the IMUs system need to be used with caution.